AIB1 is a novel target of the high‐risk HPV E6 protein and a biomarker of cervical cancer progression. Issue 8 (27th April 2022) - Miller, Jonathan; Dakic, Aleksandra; Spurgeon, Megan; Saenz, Francisco; Kallakury, Bhaskar; Zhao, Bo; Zhang, Junran; Zhu, Jian; Ma, Qin; Xu, Ying; Lambert, Paul; Schlegel, Richard; et al.
Abstract: The high‐risk human papillomaviruses (HPV‐16, ‐18) are critical etiologic agents in human malignancy, most importantly in cervical cancer. These oncogenic viruses encode the E6 and E7 proteins that are uniformly retained and expressed in cervical cancers and required for maintenance of the tumorigenic phenotype. The E6 and E7 proteins were first identified as targeting the p53 and pRB tumor suppressor pathways, respectively, in host cells, thereby leading to disruption of cell cycle controls. In addition to p53 degradation, a number of other functions and critical targets for E6 have been described, including telomerase, Myc, PDZ‐containing proteins, Akt, Wnt, mTORC1, as well as others. In this study, we identified Amplified in Breast Cancer 1 (AIB1) as a new E6 target. We first found that E6 and hTERT altered similar profiling of gene expression in human foreskin keratinocytes (HFK), independent of telomerase activity. Importantly, AIB1 was a common transcriptional target of both E6 and hTERT. We then verified that high‐risk E6 but not low‐risk E6 expression led to increases in AIB1 transcript levels by real‐time RT‐PCR, suggesting that AIB1 upregulation may play an important role in cancer development. Western blots demonstrated that AIB1 expression increased in HPV‐16 E6 and E7 expressing (E6E7) immortalized foreskin and cervical keratinocytes, and in three of four common cervical cancer cell lines as well. Then, we evaluated the expression of AIB1 in human cervical lesions and invasive carcinoma using immunohistochemical staining. Strikingly, AIB1 showed positivity in the nucleus of cells in the immediate suprabasal epithelium, while nuclei of the basal epithelium were negative, as evident in the Cervical Intraepithelial Neoplasia 1 (CIN1) samples. As the pathological grading of cervical lesions increased from CIN1, CIN2, CIN3 carcinoma in situ and invasive carcinoma, AIB1 staining increased progressively, suggesting that AIB1 may serve as a novel histological biomarker for cervical cancer development. For cases of invasive cervical carcinoma, AIB1 staining was specific to cancerous lesions. Increased expression of AIB1 was also observed in transgenic mouse cervical neoplasia and cancer models induced by E6E7 and estrogen. Knockdown of AIB1 expression in E6E7 immortalized human cervical cells significantly abolished cell proliferation. Taken together, these data support AIB1 as a novel target of HPV E6 and a biomarker of cervical cancer progression.